Адміністративно-правові та цивільно-правові юридичні факти в новому соціально-історичному вимірі - Стрельбицький, М.; Стрельбицька, Л.; Strelbitskiy, M.; Strelbitskaja, L. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розкрито роль та сутність адміністративно-правових і цивільно-правових юридичних фактів у сучасних умовах історичних соціально-економічних перетворень та державотворення в Україні. The article describes the role and nature of administrative law and civil law legal facts in the present conditions of historical socio-economic transformation of the state in Ukraine. In today's conditions of formation of government, market economy and private property institution Ukrainian legal system is going through a period of transition from the Soviet to the modern democratic system. Historical changes taking place in the administrative and legal and civil relations arising from the relevant legal facts. Legal facts in administrative law and civil law relations ensure the rights and freedoms of citizens, regulate relations between citizens and the executive authorities and civil servants, provide the ability to regulate legal relations on a contractual basis between the various economic agents in market conditions.
Administrative Legal and Civil Legal Facts in the New Socio-Historical Dimension.
Keywords: юридичні факти; правовідносини; норми адміністративного права; цивільно-правові норми; правова система; legal facts; legal; rules of administrative law; civil law; the legal system